Analysis of the community composition and bacterial diversity of the rhizosphere microbiome across different plant taxa. Issue 6 (22nd November 2018) - Lei, Shaonan; Xu, Xiaohong; Cheng, Zhiqiang; Xiong, Juan; Ma, Rongqin; Zhang, Lanlan; Yang, Xiaorong; Zhu, Yunxi; Zhang, Binghuo; Tian, Baoyu
Abstract: Rhizobacteria play an important role in bridging the soil and plant microbiomes and improving the health and growth of plants. In this study, the bacterial community structures and compositions of rhizosphere microbiomes associated with six plant species, representing two orders and three families of wild plants grown in the same field, were evaluated. The six plant species examined harbored a core and similar bacterial communities of the rhizosphere microbiome, which was dominated by members of Rhizobiales, Sphingomonadales, Burkholderiales, and Xanthomonadales of Proteobacteria, Subgroup 4 of Acidobacteria, and Sphingobacteriales of Bacteroidetes. Plant species had a significant effect on the microbial composition and Operational Taxonomic Unit (OTU) abundance of the rhizosphere microbiome. Statistical analysis indicated a significant differential OTU richness (Chao1, p  < 0.05) and bacterial diversity (Shannon index, p  < 0.0001) of the rhizosphere microbiome at the plant species, genus, or families levels. The paralleled samples from the same plant species in the PCoA and hierarchical cluster analysis demonstrated a clear tendency to group together, although the samples were not strictly separated according to their taxonomic divergence at the family or order level. The CAP analysis revealed a great proportion (44.85%) of the variations on bacterial communities could be attributed to the plant species. The results demonstrated that largely conserved and taxonomically narrow bacterial communities of the rhizosphere microbiome existed around the plant root. The bacterial communities and diversity of the rhizosphere microbiome were significantly related to the plant taxa, at least at the species levels. Abstract : In this study, the bacterial community structures and compositions of rhizosphere microbiomes associated with six plant species, representing two orders and three families of wild plants grown in the same field, were evaluated. The results revealed plants harbored a core and similar bacterial communities' structure of rhizosphere microbiome. The bacterial diversity and Operational Taxonomic Unit abundance of rhizosphere microbiome were significantly related to the plant taxa, at least at the species or family levels.